2021
DOI: 10.1021/acsami.1c05903
|View full text |Cite
|
Sign up to set email alerts
|

Manipulated Crystallization and Passivated Defects for Efficient Perovskite Solar Cells via Addition of Ammonium Iodide

Abstract: Organic–inorganic metal halide perovskite materials have been widely studied as the light absorber for efficient photovoltaics. However, perovskite layers with defective nature are typically prepared with an uncontrollable crystallization process, intrinsically limiting further advance in device performance, and thus require delicate manipulation of crystallization processes and defect density. Here, we demonstrate an ammonium-assisted crystallization of perovskite absorbers during a two-step deposition to fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…where Z s is the number of grains per unit area, which is inversely proportional to the grain size. In this study, the C≡N‐based TPE‐TCF molecule partially coordinated PbI 2 in the perovskite precursor solution and formed PbI 2 ⋅TPE‐TCF intermediate (Figure S1), which improved the crystallinity (Figure 4a) and enlarged grain size by retarding the crystallization of perovskite layer [28] . The interaction between TPE‐TCF molecules and PbI 2 in the precursor solution can reduce the nucleation rate and facilitate the perovskite grain growth due to the quick removal of solvents [31] .…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…where Z s is the number of grains per unit area, which is inversely proportional to the grain size. In this study, the C≡N‐based TPE‐TCF molecule partially coordinated PbI 2 in the perovskite precursor solution and formed PbI 2 ⋅TPE‐TCF intermediate (Figure S1), which improved the crystallinity (Figure 4a) and enlarged grain size by retarding the crystallization of perovskite layer [28] . The interaction between TPE‐TCF molecules and PbI 2 in the precursor solution can reduce the nucleation rate and facilitate the perovskite grain growth due to the quick removal of solvents [31] .…”
Section: Resultsmentioning
confidence: 75%
“…The influence of TPE‐TCF additive on the crystallization rate of the prepared perovskite film was verified by digital photographs of perovskite films (with and without TPE‐TCF additive) after annealing at 100 °C for different times (Figure S2, Supporting Information). The variation in film color indicated that TPE‐TCF addition delayed the crystallization process of the perovskite, which may be an effective method for fabricating high‐quality perovskite film with less defects [27,28] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] Interfacial engineering between the perovskite absorber and charge transport layers has been widely successful in enhancing the performance and durability of PSCs. [27][28][29] This is due to the tendency for defect or impurity formation at the interfaces, which arises from the sudden change in the lattice structure and crystal orientation. Hence, it is inevitable that a large amount of defects such as undercoordinated lead ion (Pb 2 + ), undercoordinated halides, and dangling bonds are found in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial engineering between the perovskite absorber and charge transport layers has been widely successful in enhancing the performance and durability of PSCs [27–29] . This is due to the tendency for defect or impurity formation at the interfaces, which arises from the sudden change in the lattice structure and crystal orientation.…”
Section: Introductionmentioning
confidence: 99%